Impact of Social Media Journalism on Public Opinion during Indian Elections (Journal of Informatics Education and Research, 2026)
The present study examines the impact of social media journalism on public opinion formation during Indian elections, with specific reference to credibility, agenda setting, framing of political news, and emotional appeal. Using a structured questionnaire, data were collected from a sample of 300 respondents. The reliability of the measurement scale was established using Cronbach’s alpha, indicating satisfactory internal consistency of the constructs. Exploratory Factor Analysis (EFA) was employed to identify and validate the underlying dimensions of social media journalism, and the results confirmed the adequacy of the data for factor analysis. Pearson’s correlation analysis was then used to examine the relationships between the identified dimensions and public opinion formation. The findings reveal significant positive correlations between credibility, agenda setting, framing of political news, emotional appeal, and public opinion formation, highlighting the influential role of social media journalism in shaping public perceptions during elections. The study underscores the growing importance of responsible and credible social media journalism in influencing democratic processes in the Indian electoral context.